Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2015
DOI: 10.1371/journal.pone.0134916
|View full text |Cite
|
Sign up to set email alerts
|

Quantum Two Player Game in Thermal Environment

Abstract: A two-player quantum game is considered in the presence of thermal decoherence. It is shown how the thermal environment modeled in terms of rigorous Davies approach affects payoffs of the players. The conditions for either beneficial or pernicious effect of decoherence are identified. The general considerations are exemplified by the quantum version of Prisoner Dilemma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
7
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 24 publications
(30 reference statements)
1
7
0
Order By: Relevance
“…The European Physical Journal Special Topics of geometric phases of qubits [18], thermodynamic properties of nano-systems [19] and quantum games [20]. Our present work continues and supplements our previous studies of quantum phenomena in a presence of Davies environment modelled via the Davies maps [21] related to quantum information processing.…”
supporting
confidence: 71%
“…The European Physical Journal Special Topics of geometric phases of qubits [18], thermodynamic properties of nano-systems [19] and quantum games [20]. Our present work continues and supplements our previous studies of quantum phenomena in a presence of Davies environment modelled via the Davies maps [21] related to quantum information processing.…”
supporting
confidence: 71%
“…As the Davies semigroups can be rigorously and consistently derived from microscopic models of open systems they sat-isfy thermodynamic and statistical-mechanical properties of open quantum systems such as the detailed balance condition and the Gibbs canonical distribution in the stationary regime [17]. The Davies method has been successfully used in recent studies of various problems in quantum information and physics of open quantum systems including teleportation [18], entanglement dynamics [19], quantum discord [20,21], properties of geometric phases of qubits [22], thermodynamic properties of nano-systems [23] and quantum games [24]. In this paper we consider only certain elements of Davies semigroups: the Davies maps D = D(p, A, G, ω, t) which acts as follows [25]:…”
Section: Davies Decoherencementioning
confidence: 99%
“…On the other hand, Pawela et al have recently showed that in spite of decoherence, the winning probability can be enhanced if each party performs local operations (determined by semi-definite programming) to their qubits [24]. There is also an increasing interest on playing games with Heisen- * Electronic address: MansurSah@gmail.com berg spin chains [25] and thermal entanglement [26].…”
Section: Introductionmentioning
confidence: 99%